PENGARUH INTELLECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN DIMEDIASI OLEH PROFITABILITAS - Hafidh Ahmad Rizqi Pratama; Vera Maria (Bajang Institute, 2023)
A company is founded with the aim of increasing its value, as indicated by the share price. Complete and accurate information is needed for rational decision making to produce the desired results. Businesses can leak information that will increase their value to attract investors. As a result, businesses often release information they perceive as increasing their value, which can drive up their share price. This study aims to find out the effect of Intellectual Capital, Good Corporate Governance, and Corporate Social Responsibility on company value mediated by Profitability in real estate and property sector companies listed on the Indonesia Stock Exchange in 2017 - 2022. The results show that Intellectual Capital (IC) has a negative effect on Company Value, and Good Corporate Governance (GCG) has no effect on Company Value. Corporate Social Responsibility (CSR) has no effect on company value. Profitability has a positive effect on firm value. Intellectual Capital (IC) does not affect Profitability. Good Corporate Governance (GCG) harms profitability. Corporate Social Responsibility (ICSR) does not affect profitability. Profitability does not mediate the relationship between Intellectual Capital (IC) and Firm Value. Profitability does not mediate the relationship between Good Corporate Governance (GCG) and Corporate Values. Profitability does not mediate the relationship between Corporate Social Responsibility (CSR) and Company Value.